Phonological Distinctive Features of the Ribun Dayak Language: The Phonemes and Word Syllables - Simanjuntak, Hotma; Bunau, Eusabinus (Lingua Cultura, 2023)
The research aimed to discuss the distinctive features of the Ribun Dayak language. The description of the features was essential to foster the language for future preservation, revitalization, and development. Moreover, the research focused on descriptive analysis of the language’s phonemes. The Ribun Dayak speaks the Ribun language and inhabits sub-districts Tayan Hulu, Parindu, Bonti, and Kembayan, district Sanggau, West Kalimantan. This indigenous language is vital for thousands of speakers residing in a broad zone. In effect, the language needs to be scientifically and linguistically described in terms of phonology through the research. The data collection technique was an interview and recording, and the data collecting tool was the Swadesh lexicostatistics recorded from informants using a voice recorder. Analysis of the data collected signifies that the distinctive features of language’s phonemes are vowels, diphthongs, consonants, and semi-vowels. The vowels are /i/, /u/, /e/, /o/, and /a/, and the diphthongs are <ai> and <au>. Moreover, the consonants consist of plosive, fricative, nasal, trill, and lateral, and the semi-vowel comprises /w/ and /y/. Some phonemes are consonant clusters and compounds. The onset consonant clusters are /mp/, /nt/, /nc/, and /ŋk/, while the codas consonant clusters are /nt/ and /ŋk/. Furthermore, the consonant compounds are /m-p/, /n-t/, /n-c/, /ŋ-k/, /n-s/, and /h-w/. The research also identifies three consonants with two allophones, namely /p/ with [p] and [p’], /t/ with [t] and [t’], and /k/ with [k] and [k’] while the rest only have one. The compound consonants of the language indicate phonologically conditioned interactions with asymmetrical features, which is only with voiceless consonants.